Teacher attrition in the midst of geographical, societal, and economic realities: insights from fifteen years of the Kansas teacher workforce - Lam, Chanh Bao (My University, 2025)
Leveraging longitudinal administrative data from Kansas, a state with a unique mixture of urban and rural dynamics, I examine mobility patterns of the state’s public-school teachers from 2010 through 2024. I find teacher attrition has sharply increased since the COVID-19 pandemic, especially by those who resigned from the state’s public elementary and secondary school system (i.e., leavers). I also find teachers employed in city schools are more likely to depart from the state’s school system relative to their colleagues in suburban and rural/town schools, even after accounting for the relative urbanicity of the district’s local community. Moreover, teachers serving the most marginalized and impoverished students are at the highest risks of turning over. Furthermore, STEM and SPED/ESOL teachers are significantly more likely to turn over relative to their counterparts in other subject categories. Notably, while salary and benefits are significantly associated with reductions in teacher turnover across teaching disciplines, the relationship is most pronounced among STEM and SPED/ESOL educators. These findings reflect the complex geographical, societal, and economic circumstances of Kansas, offering critical insights to targeted policy considerations for addressing the state’s teacher staffing challenges. I discuss the needs for Kansas to diversify its teacher workforce, addressing potential disparities among teacher working conditions, including among schools within the same district, as well as the potential of differential pay policies for Kansas educators amid the state’s chronic teacher shortages and changing labor markets in the post-COVID-19 era.
Keywords: Equity; Teacher retention; Teacher labor market; Teacher salary policy; Urban education